The Influence of Employee Engagement to Employee Performance at PT Telkom Bandung - Azizah, Azmi; Gustomo, Aurik (Journal of Business and Management, 2015)
Abstract. The purpose of this research is to determine the relationship about employee engagement to employee performance, and the best recommendation for the company to increase their performance. This research was taken at Service Company which is PT Telkom Bandung, one of the first state-owned monopoly companies that required providing the best service to the public in this case phone users or customers. 100 questionnaires are distributed to six departments at PT Telkom Bandung. It develop by using Gallup’s Q12 questionnaire of engagement, ASTD theory (Say, Stay, and Strive), and their relationship to employee performance. The result show that there are 5 of 12 variables indicate very good level of engagement in driver variable of employee engagement, which are: Materials and Equipment, Opportunity to Do the Best, Someone Who Cares at Work, Associates’ Committed to Quality, and Best Friend. Besides, dimension of Strive has very good level as indicator of employee performance. There are 7 of 12 variables indicate good level of engagement in driver variable of employee engagement, which are: Expectation, Recognition of Good Work, Encouraged the Development, Opinions Count, Mission/Purpose, Progress of Work, and Learn and Grow. Besides, dimension of Say and Stay has good level as indicator of employee engagement. All driver variable of employee engagement has directly influence to indicator of employee engagement and indirectly influence to employee performance, and all indicator of employee engagement has directly influence to employee performance. Keywords: employee engagement, employee performance, performance, job performance.